2022
DOI: 10.1088/1361-6463/ac5bcb
|View full text |Cite
|
Sign up to set email alerts
|

Temperature measurements of long sparks in air using time-resolved moiré deflectometry

Abstract: This paper presents an original investigation on a time-resolved moiré deflectometry for gas temperature measurements of long sparks in air. In order to perform a rigorous comparative investigation with the widely used quantitative schlieren method, we set up an orthogonal optical measurement system. The impacts of spatial resolution and exposure time on the measurement accuracy are investigated by comparing the measured radial distribution of the gas temperature and its time evolution during the same spark di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The grayscale changes in Schlieren images are quantitatively related to the deflection angle of the probing light beam, which can be used to reconstruct the refractive index distribution n(r) of the leader channel cross-section. More details about the fundamental principle of the quantitative Schlieren method can be found in [24,25]. A 6.0 MV/360.0 kJ impulse voltage generator is adopted in this work, which can perform long air gap discharge experiments with a gap length of more than 10 m. When the gap length used in experiments increases, as shown in figure 1, the distance from the collimating and convergence optical units to the high-voltage electrode has to increase accordingly to fulfill the safety insulation requirement.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The grayscale changes in Schlieren images are quantitatively related to the deflection angle of the probing light beam, which can be used to reconstruct the refractive index distribution n(r) of the leader channel cross-section. More details about the fundamental principle of the quantitative Schlieren method can be found in [24,25]. A 6.0 MV/360.0 kJ impulse voltage generator is adopted in this work, which can perform long air gap discharge experiments with a gap length of more than 10 m. When the gap length used in experiments increases, as shown in figure 1, the distance from the collimating and convergence optical units to the high-voltage electrode has to increase accordingly to fulfill the safety insulation requirement.…”
Section: Methodsmentioning
confidence: 99%
“…These can enhance the vertical component of the electric field and help to control the trajectory of the initial leader segment and avoid the displacement of the leader cross-section. The focal length of L 1 and L 2 is 1.5 m. A secondary imaging lens with a focal length of 20 cm is inserted between the knife edge and the filter instead of the long focal lens in [25], which can help to realize a spatial resolution of 60.0 µm pixel −1 . The high-speed camera is operated at a sampling rate of 200.0 kfps, which means the Schlieren image is recorded every 5.0 µs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second zero-off stage shown in figure 8, no electron density drop was detected, which means that t x may be lower than t 2 . Other studies have observed that the initial ionization channel in the air gap can be formed within a few microseconds, well before t 2 [35,36]. • Arcing stage: the arc enters the arcing stage, and its electron density gradually decreases after a rapid decline.…”
Section: Electron Number Densitymentioning
confidence: 99%